On Gumilyov as a Possible Subtext in Vladimir Nabokov’s Story "Port" - Filatov, Anton (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article deals with the absorption of Nikolai Gumilyov’s poetics and biographical legend in Vladimir Nabokov’s short story “Port”. The great importance of Gumilyov’s works and personality for the emigre writer makes it possible to classify Nikitin, the protagonist of the story, as a heroic type, whose features go back to the mythologized image of Gumilyov. The author of the article argues that the plot of the story displays semantic similarities with Gumilyov’s poem “Conversation”. The analysis of the two works allows one to discover further possible parallels with Gumilyov, which are actualized in the structure of the story (in motifs and imagery). The author comes to the conclusion that such forms of borrowing are on the part of Nabokov a conscious artistic strategy.